The C-terminus of the multi-drug efflux pump EmrE prevents proton leak by gating transport - Merissa Brousseau; Da Teng; Nathan E Thomas; Gregory A Voth; Katherine A Henzler-Wildman (eLife)
The model multi-drug efflux pump from Escherichia coli, EmrE, can perform multiple types of transport leading to different biological outcomes, conferring resistance to some drug substrates and enhancing susceptibility to others. While transporters have traditionally been classified as antiporters, symporters, or uniporters, there is growing recognition that some transporters may exhibit mixed modalities. This raises new questions about their regulation and mechanism. Here, we show that the C-terminal tail of EmrE acts as a secondary gate, preventing proton leak in the absence of drug. Substrate binding unlocks this gate, allowing transport to proceed. Truncation of the C-terminal tail (∆107-EmrE) leads to altered pH regulation of alternating access, an important kinetic step in the transport cycle, as measured by NMR. ∆107-EmrE has increased proton leak in proteoliposomes, and bacteria expressing this mutant have reduced growth. Molecular dynamics simulations of ∆107-EmrE show the formation of a water wire from the open face of the transporter to the primary binding site in the core, facilitating proton leak. In WT-EmrE, the C-terminal tail forms specific interactions that block the formation of the water wire. Together, these data strongly support the C-terminus of EmrE acting as a secondary gate that regulates access to the primary binding site.